Metaverse in Science Education: Immersive and Interactive Learning for Future - Bin Amiruddin, Mohd Zaidi; Samsudin, Achmad; Suhandi, Andi; Coştu, Bayram; Fratiwi, Nuzulira Janeusse; Suliyanah, Suliyanah (Universitas Negeri Surabaya, 2024)
Objective: This study aimed to analyze the trends, collaborations, and contributions in Metaverse-related research within the context of science education from 2021 to 2024. The research identifies the growth dynamics, key countries, institutions, and thematic keywords in Metaverse research, emphasizing its educational applications. Method: A bibliometric analysis was conducted on 64 articles from 51 sources, spanning 2021-2024 with PRISMA. The data were collected using citation metrics, keyword analysis, author collaboration, and geographical distribution of publications. VOSviewer were employed to visualize the relationships between key themes and institutions. Results: The study revealed a significant increase in research output, particularly from 2021 to 2023, with a growth rate of 100%. China and the United States emerged as the leading contributors, with distinct research patterns: China focused on national studies, while the USA engaged in more international collaborations. Keywords such as Augmented Reality, Machine Learning, and Science Education were central to the discourse, highlighting the growing intersection of technology and education. Leading institutions included the University of Zilina and Jakarta State University. Novelty:This research provides a detailed bibliometric overview of the metaverse in science education, highlighting the gap in bibliometric studies focused specifically on science education within the metaverse. It offers insights into emerging trends, key collaborations, and potential areas for further exploration.